Mental Health Help-Seeking Intentions Among International and African American College Students: An Application of the Theory of Planned Behavior - Mesidor, Jean Kesnold; Sly, Kaye F. (Journal of International Students, 2014)
This study examined the relationship between social-cognitive factors (e.g., attitudes, subjective norms, and perceived behavioral control), psychological distress, and help-seeking intentions for a sample of 111 international and African American college students. The results of this study showed that the Theory of Planned Behavior (TPB) variables (e.g., attitudes, subjective norms, and perceived behavioral control) accounted for 17.7 % of the variance in help-seeking intentions. The first hypothesis, which predicted that positive attitudes toward mental health services and perceived behavioral control would be significant predictors of the students’ intentions to seek mental health services, was partially supported. Perceived behavioral control was the strongest predictor of helpseeking intentions. Contrary to our expectations, attitudes toward mental health services were not a significant predictor of mental health seeking intentions. The second hypothesis was not supported. There was no significant difference in mean intention scores for African American college students compared to international college students.